PENGARUH DISTRIBUTIVE JUSTICE, PROCEDURAL JUSTICE , DAN INTERACTIONAL JUSTICE TERHADAP RECOVERY SATISFACTION PADA MARKETPLACE LAZADA (Studi Pada Konsumen Marketplace Lazada di Kota Malang) - Mariana, Verawinda (Jurnal Ilmiah Mahasiswa FEB, 2018)
The study aims at identifying the effect of distributive justice, procedural justice, and interactional justice on marketplace Lazada consumers’ recovery satisfaction in Malang city. This explanatory research attempts to elucidate the causal relations among variables through hypothesis testing. This study uses 100 respondents of marketplace Lazada consumers, selected using purposive sampling technique with the criteria of reaching 17 years of age at the minimum and having made at least one complaint in Lazada in the last 1 year. The research instrument was assessed using validity, reliability, and classical assumption test. The hypothesis was evaluated using t-test in SPSS 21, and the data are carefully examined using multiple regression analysis. The result of the study shows that distributive justice gives a significant influences on recovery satsifaction of Lazada consumers, procedural justice gives a significant influences on recovery satisfaction of Lazada consumers, and interactional justice also significantly influences recovery satisfaction of Lazada consumers in Malang city. Keywords: Distributive Justice, Procedural Justice, Interactional Justice, Recovery Satisfaction